(untitled) (Indian Journal of Animal Production and Management, 2016)
The importance of cattle in Hindu mythology, is well established, even today it is known by different names viz. Kamdhenu, Kapila, Nandini, Surabhi and people worship it as “Gau-Mata”, but the fact is that legendary history of Indian cow breeds from the time of glorious India to the present day times expedited that today’s Indian cow breeds need improvised policy even though Indian bovine breeds were best in the world, then what actually happened to these cow breeds. The one important reason might be the European invaders eyed the invaluable germplasm of these zebu cattle and “East India Company” started the export of superior quality of zebu cattle and bulls from India. Indian farmers were misguided to abscond their cows on the roads by spreading the air that they yield less milk. Subsequently, Indian farmers adopted exotic breeds while the foreigners started rearing zebu cattle.